Two new forest pathogens in Phaeolus (Polyporales, Basidiomycota) on Chinese coniferous trees were confirmed by molecular phylogeny - Yuan, Yuan; Wu, Ying-Da; Wang, Ya-Rong; Zhou, Meng; Qiu, Jun-Zhi; Li, De-Wei; Vlasák, Josef; Liu, Hong-Gao; Dai, Yu-Cheng (Frontiers in Microbiology, 2022)
Phaeolus schweinitzii (Fr.) Pat. was originally described from Europe and considered as a common forest pathogen on conifers in North Hemisphere. Our molecular phylogeny based on samples from China, Europe and North America confirms that Phaeolus schweinitzii is a species complex, including six taxa so far. Phaeolus schweinitzii sensu stricto has a distribution in Eurasia, the samples from Northeast and Southwest China are distantly related to P. schweinitzii sensu stricto, and two new species are described after morphological, phylogenetic and geographical analyses. The species growing on Larix, Picea and Pinus in Northeast China is described as Phaeolus asiae-orientalis. Another species mostly occurring on Pinus yunnanensis in Southwest China is named as Phaeolus yunnanensis. In addition, three taxa distributed in North America are different from Phaeolus schweinitzii sensu stricto. Phaeolus tabulaeformis (Berk.) Pat. is in Southeast North America, “Phaeolus schweinitzii-1” in Northeast North America and “Phaeolus schweinitzii-2” in West North America.